AT-101 enhances gefitinib sensitivity in non-small cell lung cancer with EGFR T790M mutations. Issue 1 (December 2016) - Zhao, Ren; Zhou, Shun; Xia, Bing; Zhang, Cui-ying; Hai, Ping; Zhe, Hong; Wang, Yan-yang
Abstract Background Although epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) have become the standard care of patients with advanced EGFR-mutant non-small cell lung cancer (NSCLC), development of acquired resistance is inevitable. A secondary mutation of threonine 790 (T790M) is associated with approximately half of the cases of acquired resistance. Strategies or agents to overcome this type of resistance are still limited. In this study, enhanced antitumor effect of AT-101, a-pan-Bcl-2 inhibitor, on gefitinib was explored in NSCLC with T790M mutation. Methods The effect of cotreatment with AT-101 and gefitinib on the viability of NSCLC cell lines harboring acquired T790M mutation was investigated using the MTT assay. The cellular apoptosis of NSCLC cells after cotreatment with AT-101 and gefitinib was assessed by FITC-annexin V/PI assay and Western blots analysis. The potential underlying mechanisms of the enhanced therapeutic effect for AT-101 was also studied using Western blots analysis. The in vivo anti-cancer efficacy of the combination with AT-101 and gefitinib was examined in a mouse xenograft model. Results In this study, we found that treatment with AT-101 in combination with gefitinib significantly inhibited cell proliferation, as well as promoted apoptosis of EGFR TKIs resistant lung cancer cells. The apoptotic effects of the use of AT-101 was related to the blocking of antiapoptotic protein: Bcl-2, Bcl-xl, and Mcl-1 and downregrulation of the molecules in EGFR pathway. The observed enhancements of tumor growth suppression in xenografts supported the reverse effect of AT-101 in NSCLC with T790M mutation, which has been found in in vitro studies before. Conclusions AT-101 enhances gefitinib sensitivity in NSCLC with EGFR T790M mutations. The addition of AT-101 to gefitinib is a promising strategy to overcome EGFR TKIs resistance in NSCLC with EGFR T790M mutations.